Analisis Efisiensi Perbankan Berdasarkan Rasio Keuangan pada PT. Bank Rakyat Indonesia - Jultantyo, Satryo; Hasan, Khojanah; Anggarani, Dwi (AKSIOMA : Jurnal Sains Ekonomi dan Edukasi, 2025)
The purpose of this study is to determine the efficiency level of PT. Bank Rakyat Indonesia based on financial ratios. The researcher used a quantitative method with secondary data. In this study, all financial report data from PT. Bank Rakyat Indonesia for the period 2021 to 2023 will serve as the research unit of analysis. This means the researcher will use a census approach, where all elements of the population are the objects of study. This study uses data collection techniques through documentation. Data analysis techniques are the process of processing and interpreting collected data to obtain meaningful and relevant information for the research objectives. Banking efficiency analysis using the BOPO (Operating Costs to Operating Income) ratio involves several systematic steps to obtain a clear picture of a bank's operational performance. The results of the study indicate that the BOPO ratio of PT. Bank Rakyat Indonesia's performance from 2021 to 2023 showed a very positive and consistent trend. The BOPO ratio decreased significantly from 78.14% in 2021 to 69.16% in 2022, and continued to improve to 67.24% in 2023. This decline clearly indicates that PT. Bank Rakyat Indonesia has successfully improved its operational efficiency sustainably during this period. This efficiency performance also exceeds the national banking industry average, which tends to be higher, confirming BRI's position as one of the banks with excellent operational expense management in Indonesia.